Biological effects of passive scattering and spot scanning proton beams at the distal end of the spread-out Bragg peak in single cells and multicell spheroids. (4th May 2021) - Nomura, Kento; Iwata, Hiromitsu; Toshito, Toshiyuki; Omachi, Chihiro; Nagayoshi, Junpei; Nakajima, Koichiro; Ogino, Hiroyuki; Shibamoto, Yuta
Abstract: Purpose: The present study investigated the biological effects of spot scanning and passive scattering proton therapies at the distal end region of the spread-out Bragg peak (SOBP) using single cell and multicell spheroids. Materials and methods: The Geant4 Monte Carlo simulation was used to calculate linear energy transfer (LET) values in passive scattering and spot scanning beams. The biological doses of the two beam options at various points of the distal end region of SOBP were investigated using EMT6 single cells and 0.6-mm V79 spheroids irradiated with 6 and 15 Gy, respectively, by inserting the fractions surviving these doses onto dose-survival curves and reading the corresponding dose. Results: LET values in the entrance region of SOBP were similar between the two beam options and increased at the distal end region of SOBP, where the LET value of spot scanning beams was higher than that of passive scattering beams. Increases in biological effects at the distal end region were similarly observed in single cells and spheroids; biological doses at 2–10 mm behind the distal end were 4.5–57% and 5.7–86% higher than physical doses in passive scattering and spot scanning beams, respectively, with the biological doses of spot scanning beams being higher than those of passive scattering beams ( p < .05). Conclusions: In single cells and spheroids, the effects of proton irradiation were stronger than expected from measured physical doses at the distal end of SOBP and were correlated with LET increases.